Materializing the Web of Linked Data - Konstantinou, Nikolaos; Spanos, Dimitrios-Emmanuel.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book explains the Linked Data domain by adopting a bottom-up approach: it introduces the fundamental Semantic Web technologies and building blocks, which are then combined into methodologies and end-to-end examples for publishing datasets as Linked Data, and use cases that harness scholarly information and sensor data. It presents how Linked Data is used for web-scale data integration, information management and search. Special emphasis is given to the publication of Linked Data from relational databases as well as from real-time sensor data streams. The authors also trace the transformation from the document-based World Wide Web into a Web of Data. Materializing the Web of Linked Data is addressed to researchers and professionals studying software technologies, tools and approaches that drive the Linked Data ecosystem, and the Web in general.
Introduction: Linked Data and the Semantic Web -- Technical Background -- Deploying Linked Open Data: Methodologies and Software Tools -- Creating Linked Data from Relational Databases -- Generating Linked Data in Real-Time from Sensor Data Streams -- Conclusions.
Keywords: Data mining; Information storage and retrieva; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Information Systems Applications (incl. Internet).